Oligo[poly(ethylene glycol)fumarate] Hydrogel Enhances Osteochondral Repair in Porcine Femoral Condyle Defects - Hui, James H. (Springer-Verlag, 2012)
BACKGROUND: Management of osteochondritis dissecans remains a challenge. Use of oligo[poly(ethylene glycol)fumarate] (OPF) hydrogel scaffold alone has been reported in osteochondral defect repair in small animal models. However, preclinical evaluation of usage of this scaffold alone as a treatment strategy is limited. QUESTIONS/PURPOSES: We therefore (1) determined in vitro pore size and mechanical stiffness of freeze-dried and rehydrated freeze-dried OPF hydrogels, respectively; (2) assessed in vivo gross defect filling percentage and histologic findings in defects implanted with rehydrated freeze-dried hydrogels for 2 and 4 months in a porcine model; (3) analyzed highly magnified histologic sections for different types of cartilage repair tissues, subchondral bone, and scaffold; and (4) assessed neotissue filling percentage, cartilage phenotype, and Wakitani scores. METHODS: We measured pore size of freeze-dried OPF hydrogel scaffolds and mechanical stiffness of fresh and rehydrated forms. Twenty-four osteochondral defects from 12 eight-month-old micropigs were equally divided into scaffold and control (no scaffold) groups. Gross and histologic examination, one-way ANOVA, and one-way Mann-Whitney U test were performed at 2 and 4 months postoperatively. RESULTS: Pore sizes ranged from 20 to 433 μm in diameter. Rehydrated freeze-dried scaffolds had mechanical stiffness of 1 MPa. The scaffold itself increased percentage of neotissue filling at both 2 and 4 months to 58% and 54%, respectively, with hyaline cartilage making up 39% of neotissue at 4 months. CONCLUSIONS: Rehydrated freeze-dried OPF hydrogel can enhance formation of hyaline-fibrocartilaginous mixed repair tissue of osteochondral defects in a porcine model. CLINICAL RELEVANCE: Rehydrated freeze-dried OPF hydrogel alone implanted into cartilage defects is insufficient to generate a homogeneously hyaline cartilage repair tissue, but its spacer effect can be enhanced by other tissue-regenerating mediators.